Participation of Women in the Notarial Public Deed of the 16th Century. From the Constriction of the Marital Licence to the Fullness of Widowhood - Rivera, Alicia Marchant; Cebrian, Lorena Barco (European Scientific Journal, ESJ, 2017)
This study intends to analyse the participation of the married woman and the widow in the notarial public deed of the 16th century, in Spain, in light of the notarial forms and treatises of the time and the process itself of executing a notarial public deed. Visigothic Law would gather, to certain extent, Roman limitations and the openness brought by the Christian doctrine, resulting in the different legal systems of High Medieval times, when the married woman needed a licence from her husband in order to act. Spanish Law 56 of Toro would regulate the marital licence as a general system and compulsory requirement for the valid intervention of the married woman. In the beginning of the 16th century, not a few women executed notarial deeds and wrote royal letters related to registering as residents, returning properties and shortening litigations.